Autologous Alternative Vein Grafts for Infrainguinal Bypass in the Absence of Single-Segment Great Saphenous Vein: A Single-Center Study - Biroš, Ernest; Staffa, Robert; Krejčí, Miroslav; Novotný, Tomáš; Skotáková, Monika; Bobák, Robert (Annals of vascular surgery, 2024)
BACKGROUND: Alternative autologous veins can be used as a conduit when adequate great saphenous vein is unavailable. We analyzed the results of our infrainguinal bypasses after adopting upper extremity veins in our practice. METHODS: This is a single-center observational study involving all patients whose infrainguinal bypass involved the use of upper extremity veins between April 2019, when we began using arm veins, and February 2023. RESULTS: During the study period, 49 bypasses were done in 48 patients; mean age 68.1 ± 9.8; men 32 (66.7%); body mass index 28.0 ± 4.8; indications for surgery: chronic limb threatening ischemia 41 (83.7%); acute limb ischemia 3 (6.1%); complications of previous prosthetic 3 (6.1%), or autologous 2 (4.1%) bypass grafts. Vein splicing was used in 43 (87.8%) bypasses with 3-segment grafts being the most common (26; 53.1%). There were 24 (49.0%) femorotibial, 11 (22.4%) femoropopliteal, 9 (18.4%) femoropedal, and 5 (10.2%) extension jump bypass procedures. Eighteen (36.7%) operations were redo surgeries. Twenty-one (42.9%) bypasses were formed using only arm veins. The median follow-up was 12.9 months (4.5-24.2). Two bypasses occluded during the first 30 postoperative days (2/49; 4.1%). Overall 30-day, 1-year, and 2-year primary patency rates were 93.7% ± 3.5%, 84.8% ± 5.9%, and 80.6% ± 6.9%, and secondary patency (SP) rates were 95.8% ± 2.9%, 89.2% ± 5.3%, and 89.2% ± 5.3%. One-segment grafts had better patencies than 2-, 3-, and 4-segment grafts (1-year SP 100% ± 0% vs 87.6% ± 6.0%). Two-year amputation-free survival was 86.8% ± 6.5%; 2-year overall survival was 88.2% ± 6.6%. CONCLUSIONS: Integration of arm vein grafts in infrainguinal bypass practice can be done safely with low incidences of perioperative graft failure. One-segment grafts had better patencies than spliced vein grafts. The achieved early patency and amputation-free survival rates strongly encourage their use. In the absence of a single-segment great saphenous vein, upper extremity vein grafts should be the preferred conduit choice.
Keywords: záchrana končetiny; vena saphena; Veins; retrospektivní studie; autologní transplantace; Aged; Treatment Outcome; Aged, 80 and over; Time Factors; Retrospective Studies; lidé středního věku; Vascular Grafting; transplantace cév; senioři; Saphenous Vein; Limb Salvage; lidé; časové faktory; Risk Factors; Middle Aged; amputace; Amputation, Surgical; reoperace; Female; Upper Extremity; výsledek terapie; okluze cévního štěpu; senioři nad 80 let; Reoperation; Male; ženské pohlaví; Humans; mužské pohlaví; onemocnění periferních arterií; Graft Occlusion, Vascular; Transplantation, Autologous; rizikové faktory; horní končetina; Peripheral Arterial Disease; průchodnost cév; Vascular Patency; vény